(untitled) (Педагогіка вищої та середньої школи, 2008)
The problem of necessity of formation of the contemporary young educated man’s informational culture has been revealed. The article stresses on importance of informational culture high level, which stimulates the improvement of training process; provides the availability & effective ness of educational process; the readiness of young generation for vital activity in the information society.